PANDEMI COVID-19: KETERPURUKAN DAN KEBANGKITAN PERTANIAN STRATEGI MEMPERTAHANKAN KETERSEDIAAN PANGAN POKOK RUMAH TANGGA PETANI PADI PADA MASA PANDEMI COVID-19 (Studi Kasus: Desa Pelem, Kecamatan Gabus, Kabupaten Grobogan, Jawa Tengah) - Faatihah A'dani; Yayat Sukayat; Iwan Setiawan; M. Gunardi Judawinata (Universitas Galuh Ciamis, 2021)
Food security in a household can be measured with stability and security of an availability household staple food. COVID-19 has an impact on the agricultural sector and farmers, thus affecting their income and automatically affecting their household food availability. To avoid the crisis caused by this pandemic, small farmers must carry out unusual strategies to maintain food availability in their households. The aim of this study is to determine how Covid-19 impacted rice farmer’s household food availability and their strategies to cope with this uncertain situation. This research is using qualitative research with a case study approach at Pelem Village, Grobogan, Central Java. The sample selection using purposive and snowball sampling method. The results of this research showed contradicting responses based on the farmer’s status (agriculture as the main job or just a side job) and their access to another source of income that affected how Covid-19 Impacted their activities and rejected that Covid-19 Impacted their activities. In this study, it is shown that the cultural factors of farmers who live simply and who plant food commodities are more resistant than the other farmers who plant other types of commodity and lower class income society in the city. Their strategies include selling a larger proportion of their yields because the harvest prices decreased, taking side jobs outside the agriculture sector, taking more from their own stocks and local granary and also received assistance from the government such as (BST,BPNT,JPS).